PENGEMBANGAN MAKANAN KHAS BALI SEBAGAI WISATA KULINER (CULINARY TOURISM) DI DESA SEBATU KECAMATAN TEGALALANG GIANYAR - Eka Putri, I. A. Trisna; Sulistyawati, A. Sri; Suark, F. Maharani; Ariani, N. M. (Buletin Udayana Mengabdi; Vol 12 No 1 (2013): Volume 12 No.1 – April 2013, 2013)
Sebatu village has its special characteristics of traditional foods and beverages which can be developed as culinary tourism. Besides the taste and form of the foods , the cooking process from the ingredients until become the ready food, and the presentation of the foods can be the interesting attraction to offer. Organizing the traditional food and beverages of Sebatu Village which is the part of the daily life in this village need to be developed as the interaction tools and media among the local community and the tourist. The activities form such as; eating and enjoy the food together ( for lunch or dinner, etc ), organizing the restaurant, coffee shop, or cafe in the strategic location surrounding the village, cooking courses for the women organization and the other programs. These programs of course need the education, training exercise and also the workshop how to make good presentation, improve the quality according to international standard, and also the sanitation and hygiene. Since Sebatu Village developes to become a Tourism Village as one of the destination, the organized traditional food and beverages business can be developed as the culinary tourism so that the local community can interacte directly with the tourists in Gianyar. The type of culinary to be developed in Sebatu such as : Jukut Ares as a appetizer. Nasi Sela, Tipat Cantok, Betutu, Be Guling, Lawar Gedang, Jukut Urab as the main course. Tape Ketan and Jaje Uli,, Jaje Dadar, Jaje Timus, Kolak Biu/Sela as the dessert. All of these culinary can be adapted to the international gastronomy from the form, purpose and essence so that it can be presented and offered to the tourists